A Controversial Make-Over of a ‘Make-Believe’ Heritage—The Transformation of Guangrenwang Temple - Lui Tam (Architecture, 2024)
This article discusses issues related to sustainable heritage management in China and problematises two dichotomies in heritage practices and research: the ‘Eastern/Western’ approaches and the tangible–intangible divide. It addresses these issues by examining the dramatic ‘make-over’ project of Guangrenwang Temple in Shanxi Province, China. The ‘make-over’ project transformed a small rural temple with a ninth-century timber structure into an architectural history museum, with a combination of private, public, and crowd-sourced funding. A real-estate corporation played a significant role in the project’s initiative and organised a large-scale national and international publicity campaign around the project. Previously unknown to most laypeople in China, the temple attracted much debate since the project’s completion, revolving around its ‘cultural legitimacy’, the design’s appropriateness, the sustainability of the revitalisation, and the implications of the project to its ‘heritage value’ and authenticity. This article traces the opinions, actions, and effects of the temple’s heritage assemblage and reveals the causal powers contributing to the emergence and transformation of associations within. It further questions the project team’s claims regarding the project’s effects on the historic setting’s authenticity and its long-term social impact on the relationship between the temple and its community. It reveals five controversies regarding the choice of its curation theme, architectural language, decision-making, and management models. The complexities manifested in the actors’ actions and effects demonstrate the ambiguous boundaries between the tangible and the intangible, and the perceived ‘Western’ and ‘Eastern’ approaches.